LEISHMANIA DONOVANI IN THE PERIPHERAL BLOOD - Young, Charles W. (The Rockefeller University Press, 1923)
1. The effect of human red cells and serum on the growth of Leishmania donovani has been studied and a blood culture method devised, based on these findings. 2. The distribution of blood platelets and of the different varieties of leucocytes in the strata of centrifugalized diluted blood has been investigated, and also the distribution of Leishman-Donovan bodies, extracellular and intracellular, in these strata. 3. The effect of treatment with antimony on the cultivability of Leishmania donavani has been studied.